A New Algorithm of Frequency Offset Estimation - Qing-Ming Yi; Min Shi (2007 International Conference on Machine Learning and Cybernetics, 2007)
Frequency synchronization for OFDM is very important because the carrier frequency offset (CFO) will damage the performance. Based on the correlation between the front half-symbol and the back half-symbol in BPSK modulation, a cost function is deduced which varies with the carrier frequency offset as a sine function, and then a new carrier frequency offset estimation algorithm is presented. Then frequency offset estimation can be conducted based on this cost function. At the same time, the method that simplifies iterative calculation is given, which makes the algorithm suitable for hardware implementation and practical application. The results are also suitable for OFDM signal based on QPSK and 8PSK modulation.